First in situ observations of the goblin shark Mitsukurina owstoni - Aaron B. Judah; Alan J. Jamieson; Sarah R. D. Bingo; Megan E. Cundy; David A. Ebert; Steven Auscavitch; Harold K. Carlson; Tiffany Nicole G. Cunanan; Hayley B. Sims; Meagan Putts (Journal of Fish Biology, 2026)
We report the first live in situ observations of the iconic goblin shark ( Mitsukurina owstoni ) on a seamount near Jarvis Island in 2019 and on the slope of the Tonga Trench in 2024. Past observations are restricted to specimens hauled to the surface, resulting in limited knowledge of this species' ecology. These observations extend its known geographic and depth range considerably, and extend the depth range of lamniform sharks by 108 m. To further clarify habitat preferences and assess conservation status, further sampling, particularly with remote video, is required.

Recent Results on Science and Innovation Related to Electrical Processes of Thunderstorms - Christoph Köhn; Torsten Neubert; Martin Füllekrug; Ute Ebert; Sander Nijdam; Olivier Chanrion; Nikolai Østgaard; Martino Marisaldi; Serge Soula; Joan Montanyà; Francisco Gordillo-Vázquez; Alejandro Luque; et al. (Surveys in Geophysics, 2025)

Resistance exercise training in older men reduces ATF4-activated and senescence-associated mRNAs in skeletal muscle - Zachary D. Von Ruff; Matthew J. Miller; Tatiana Moro; Paul T. Reidy; Scott M. Ebert; Elena Volpi; Christopher M. Adams; Blake B. Rasmussen (GeroScience, 2025)
Sarcopenia increases the risk of frailty, morbidity, and mortality in older adults. Resistance exercise training improves muscle size and function; however, the response to exercise training is variable in older adults. The objective of our study was to determine both the age-independent and age-dependent changes to the transcriptome following progressive resistance exercise training. Skeletal muscle biopsies were obtained before and after 12 weeks of resistance exercise training in 8 young (24 ± 3.3 years) and 10 older (72 ± 4.9 years) men. RNA was extracted from each biopsy and prepared for analysis via RNA sequencing. We performed differential mRNA expression, gene ontology, and gene set enrichment analyses. We report that when comparing post-training vs pre-training 226 mRNAs and 959 mRNAs were differentially expressed in the skeletal muscle of young and older men, respectively. Additionally, 94 mRNAs increased, and 17 mRNAs decreased in both young and old, indicating limited overlap in response to resistance exercise training. Furthermore, the differential gene expression was larger in older skeletal muscle. Finally, we report three novel findings: 1) resistance exercise training decreased the abundance of ATF4-activated and senescence-associated skeletal muscle mRNAs in older men; 2) resistance exercise-induced increases in lean mass correlate with increased mRNAs encoding mitochondrial proteins; and 3) increases in muscle strength following resistance exercise positively correlate with increased mRNAs involved in translation, rRNA processing, and polyamine metabolism. We conclude that resistance exercise training elicits a differential gene expression response in young and old skeletal muscle, including reduced ATF-4 activated and senescence-associated gene expression.

Crude glycerol as a sustainable source for carbon-based photoluminescent material - Amanda T. Vieira; Hevelyn V. Ebert; Eralci M. Therézio; Ailton J. Terezo; Ariane I. Barros; Adriano B. de Siqueira; Mario R.S. Soares (Biomass and Bioenergy, 2025)

A novel SARS-CoV-2 modified live vaccine with an optimized safety profile induces sterile immunity in Syrian hamsters - A. Breithaupt; T. Britzke; J. Schön; G.T. Barut; N.J. Halwe; L. Ulrich; N. Ebert; B. Trüeb; M. Brügger; V. Thiel; M. Beer; D. Hoffmann (Journal of Comparative Pathology, 2024)

Spatial extent and isolation of marine artificial structures mediate fish density - Virginia A. Gilliland; Avery E. Fessler; Avery B. Paxton; Erik F. Ebert; Ryan M. Tharp; Brendan J. Runde; Nathan M. Bacheler; Jeffrey A. Buckel; J. Christopher Taylor (Frontiers in Marine Science, 2023)
Installations of artificial structures in coastal oceans create de facto habitat for marine life. These structures encompass wide varieties of physical characteristics, reflecting their multiple, diverse purposes and creating a need to understand which characteristics maximize fish habitat. Here, we test how physical characteristics – horizontal area, vertical relief, and spatial isolation – relate to fish density from echosounder surveys over artificial structures like concrete pipes, train boxcars, and ships purposely sunk to function as reefs. Echosounder mapping of 31 artificial reef structures and associated fish across a 200 km linear length of the continental shelf of North Carolina, USA, revealed that structures with greater horizontal area and vertical relief host higher fish densities than smaller, shorter structures. Artificial structure spatial arrangement also relates to fish density, as isolated structures are generally associated with greater localized fish densities than structures closer to one another. Patterns in the relationships between fish density and reef characteristics differed for schooling fish, as there was some evidence that reefs of intermediate area exhibited higher schooling fish density. These results suggest that intentional design and spatial arrangement of marine built structures like artificial reefs relates to and can be deliberately incorporated into siting and deployment decisions to enhance their role as fish habitat.

The transcription regulator ATF4 is a mediator of skeletal muscle aging - Matthew J. Miller; George R. Marcotte; Nathan Basisty; Cameron Wehrfritz; Zachary C. Ryan; Matthew D. Strub; Andrew T. McKeen; Jennifer I. Stern; Karl A. Nath; Blake B. Rasmussen; Andrew R. Judge; Birgit Schilling; et al. (GeroScience, 2023)
Aging slowly erodes skeletal muscle strength and mass, eventually leading to profound functional deficits and muscle atrophy. The molecular mechanisms of skeletal muscle aging are not well understood. To better understand mechanisms of muscle aging, we investigated the potential role of ATF4, a transcription regulatory protein that can rapidly promote skeletal muscle atrophy in young animals deprived of adequate nutrition or activity. To test the hypothesis that ATF4 may be involved in skeletal muscle aging, we studied fed and active muscle-specific ATF4 knockout mice (ATF4 mKO mice) at 6 months of age, when wild-type mice have achieved peak muscle mass and function, and at 22 months of age, when wild-type mice have begun to manifest age-related muscle atrophy and weakness. We found that 6-month-old ATF4 mKO mice develop normally and are phenotypically indistinguishable from 6-month-old littermate control mice. However, as ATF4 mKO mice become older, they exhibit significant protection from age-related declines in strength, muscle quality, exercise capacity, and muscle mass. Furthermore, ATF4 mKO muscles are protected from some of the transcriptional changes characteristic of normal muscle aging (repression of certain anabolic mRNAs and induction of certain senescence-associated mRNAs), and ATF4 mKO muscles exhibit altered turnover of several proteins with important roles in skeletal muscle structure and metabolism. Collectively, these data suggest ATF4 as an essential mediator of skeletal muscle aging and provide new insight into a degenerative process that impairs the health and quality of life of many older adults.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; Peter M. Kyne; Riley A. Pollom; David A. Ebert; Colin A. Simpfendorfer; Gina M. Ralph; Shaikha S. Al Dhaheri; K. V. Akhilesh; Khadeeja Ali; Mohamud Hassan Ali; Tariq M. S. Al Mamari; K. K. Bineesh; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.

Arsenic-containing hydrocarbons: effects on gene expression, epigenetics, and biotransformation in HepG2 cells - S. M. Müller; H. Finke; F. Ebert; J. F. Kopp; F. Schumacher; B. Kleuser; K. A. Francesconi; G. Raber; T. Schwerdtle (Archives of Toxicology, 2018)

Redescription of Scymnodon ichiharai Yano and Tanaka 1984 (Squaliformes: Somniosidae) from the western North Pacific, with comments on the definition of somniosid genera - William T. White; Diego F. B. Vaz; Hsuan-Ching Ho; David A. Ebert; Marcelo R. de Carvalho; Shannon Corrigan; Elisabeth Rochel; Murilo de Carvalho; Sho Tanaka; Gavin J. P. Naylor (Ichthyological Research, 2015)

Comparison of particle-tracking and lumped-parameter age-distribution models for evaluating vulnerability of production wells to contamination - S. M. Eberts; J. K. Böhlke; L. J. Kauffman; B. C. Jurgens (Hydrogeology Journal, 2012)

A map of human impacts to a “pristine” coral reef ecosystem, the Papahānaumokuākea Marine National Monument - K. A. Selkoe; B. S. Halpern; C. M. Ebert; E. C. Franklin; E. R. Selig; K. S. Casey; J. Bruno; R. J. Toonen (Coral Reefs, 2009)

Exploiting the potential of indigenous fruit trees: Grewia tenax (Forssk.) Fiori in Sudan - J. Gebauer; K. El-Siddig; B. A. El Tahir; A. A. Salih; G. Ebert; K. Hammer (Genetic Resources and Crop Evolution, 2007)

Reconstitution of cyanogenesis in barley (Hordeum vulgare L.) and its implications for resistance against the barley powdery mildew fungus - Kirsten A. Nielsen; Maria Hrmova; Janni Nyvang Nielsen; Karin Forslund; Stefan Ebert; Carl E. Olsen; Geoffrey B. Fincher; Birger Lindberg Møller (Planta, 2006)

Galantamine: a cholinergic patch in the treatment of alcoholism: a randomized, placebo-controlled trial - K. Mann; K. Ackermann; A. Diehl; D. Ebert; G. Mundle; H. Nakovics; T. Reker; G. Richter; L. G. Schmidt; M. Driessen; K. Rettig; K. Opitz; et al. (Psychopharmacology, 2006)

Linking Land Cover and Water Quality in New York City’S Water Supply Watersheds - M. H. Mehaffey; M. S. Nash; T. G. Wade; D. W. Ebert; K. B. Jones; A. Rager (Environmental Monitoring and Assessment, 2005)

How to Improve Quality Assurance in Fluorometry: Fluorescence-Inherent Sources of Error and Suited Fluorescence Standards - U. Resch-Genger; K. Hoffmann; W. Nietfeld; A. Engel; J. Neukammer; R. Nitschke; B. Ebert; R. Macdonald (Journal of Fluorescence, 2005)

Mixed inoculations of a microsporidian parasite with horizontal and vertical infections - Dita B. Vizoso; Dieter Ebert (Oecologia, 2005)

Escitalopram versus citalopram: the surprising role of the R-enantiomer - Connie Snchez; KlausP. Bges; Bjarke Ebert; ElinHeldbo Reines; Claus Braestrup (Psychopharmacology, 2004)

Origin of facultative heterochromatin in the endosperm ofGagea lutea (Liliaceae) - J. Greilhuber; I. Ebert; A. Lorenz; B. Vyskot (Protoplasma, 2000)

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Regional impact analysis of climate change on natural and managed forests in the Federal State of Brandenburg, Germany - P. Lasch; M. Lindner; B. Ebert; M. Flechsig; F.-W. Gerstengarbe; F. Suckow; P.C. Werner (Environmental Modeling & Assessment, 1999)

Serotonin 1A receptor autoradiography during alcohol-withdrawal kindling - J. Ulrichsen; Bjarke Ebert; Steven Haugbøl; B. Bech; Christian Holkmann Olsen; Nils Henrik Diemer; Ralf Hemmingsen (Psychopharmacology, 1997)

Einfluß zentralnervöser koordination im Sinne v. HOLSTs auf die Steuerung von Atem- und Extremitätenmotorik des Menschen - B. Raßler; S. Waurick; D. Ebert (Biological Cybernetics, 1990)